Theoretical Aspects in Forming Complex Structure Signal - Manaenko, Sergey; Dvornikov, Sergey; Pshenichnikov, Alexander (Informatika i avtomatizaciâ (Online), 2021)
Receiving and transmitting paths of modern radio communication systems are built on the basis of an open structure that provides hierarchical differentiation of access to the provided telecommunication services. However, this approach does not exclude the possibility of access to the transmitted content by unauthorized users. Hiding information by methods of cryptographic protection in such a situation only activates additional interest in transmission, therefore the most pragmatic solution is to use signals of a complex structure, which significantly complicate or even exclude the extraction of information from them by third-party users. The problem of regulating access selection in the development and design radio system elements is rather multifaceted and has a high degree of complexity. One of the directions for solving problems in this subject area is based on the well-known approaches to expanding the signal base, however, algorithms for their practical implementation were obtained without taking into account the limitations on the allocated resource and the very fact of using these algorithms. Based on the theory of systems and the general theory of communication, an approach to the formation of signal structures of a complex structure has been developed, which ensures an increase in the properties of their structural secrecy in relation to unauthorized users. At the same time, the known solutions at the physical level of signal spaces were refined, which made it possible to formalize the procedures for the formation of radio signals with specified properties. The method of formalizing the function of displaying the signal space based on the allocation of stochastic properties of pseudo-random sequences has been substantiated, which made it possible to ensure the uncertainty of their structure in case of unauthorized processing. The approbation of the proposed approach is given on the example of the formation of quadrature modulation signals, taking into account the subsequent analysis of their properties from various positions of legitimate and illegitimate users. The results obtained confirm the uncertainty during illegitimate processing with a slight deterioration in the noise immunity properties of radio communication systems. In general, this allows to conclude the adequacy of theoretical solutions. As an example, constellation diagrams of signals at the output of a quadrature receiver are presented. The set of proposed technical solutions presented in the work determines the novelty of this approach. The scientific problem to be solved belongs to the class of problems of synthesis of signals of complex structures.